Impact of NIMART training on HIV management in Ngaka Modiri Molema District, North WEST province - Sheillah Hlamalani Mboweni; Lufuno Makhado (Elsevier, 2019)
Background: The purpose of NIMART training is to upscale the capacity of PNs with knowledge, skills, confidence and competencies to provide comprehensive and quality health care services to PLWH and thereby improve the performance of the HIV programme. Therefore, this study evaluates the impact of NIMART training on the implementation of the HIV programme to identify gaps and extend best practices. Objectives: The objective of the study is to determine and evaluate the impact of NIMART training on HIV programme in order to make recommendations leading to effective training and implementation. Methods: A quantitative descriptive design for programme evaluation was used to examine the impact of NIMART training on the implementation of the HIV programme. The study was conducted in rural districts of the North West province. A stratified simple random sampling method was used to select n = 10 PHC fixed clinics and community health centres that met the inclusion criteria. Five sub-districts were selected to participate in the study to allow a greater degree of representativeness. The statistics of ART indicators were collected from the DHIS from January 2012 to December 2016. These ART indicators have been measured against the number of PNs trained on NIMART. Descriptive statistics were used to analyse data. Results: The study results revealed ineffectiveness in the implementation of NIMART training programme and inefficiency in the management of HIV as there is no steady increase of new ART initiation in adults, children, and ANC pregnant women and below 90%, despite 99% of PHC selected facilities having 75% on PNs trained on NIMART, 42.8% were not certificated for competence and only 23% not trained, including the changes in eligibility criteria for treatment, introduction of PMTCT policy and universal test and treat (UTT) in September 2016. Sustainability of patient on ART is poor as the study results revealed fluctuation in both adults and children TROA and high LTFU at an average of 14%. Again, of Viral load collection (54%) & Viral load suppression (56%) rate at 12 months after ART initiation is far below the 90% target and had negative impact on patient treatment outcomes including decanting of stable patients out of the overcrowded facilities. However, adult patient death after 12 months of starting treatment declined. Conclusion and Recommendations: There is a significant impact of NIMART training on HIV management with regard to increased access to PHC facilities. However, challenges still exist that reveal poor quality of HIV management, non-compliance to guidelines and monitoring of treatment effectiveness despite PNs trained on NIMART. Challenges or barriers that lead to the identified gaps need to be investigated in order to make recommendations that strengthen NIMART training and implementation. Keywords: NIMART- Nurse initiated management of anti-retroviral therapy training, HIV programme, Impact, PHC facilities, Professional nurses